Multidisciplinary Approach to Neoadjuvant Endocrine Therapy in Breast Cancer: A Comprehensive Review - Reinert, Tomás; Ramalho, Susana; Gonçalves, Rodrigo; Barrios, Carlos Henrique; Graudenz, Marcia Silveira; Bines, José (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Breast cancer is the most common type of cancer and the leading cause of cancer-related death among women worldwide. Hormone receptor-positive (HR+) tumors represent the most common form of this disease, with more than 70% of breast cancers expressing these receptors. Response and benefit to neoadjuvant chemotherapy (NCT) varies according to HR expression, with lower responses in luminal tumors as compared with hormone receptor-negative (HR-) and human epidermal growth factor receptor 2-positive (HER2+) tumors. Neoadjuvant endocrine therapy (NET) is an option for selected patients with HR+ locally advanced breast cancer. Neoadjuvant endocrine therapy has a favorable toxicity profile, and is associated with benefits such as having low cost and being more easily available even for cancer care professionals outside major urban areas or tertiary centers. These factors are particularly relevant, as 70% of breast cancer deaths occur in women from low-income and middle-income countries. Additionally, NET is being increasingly explored, not simply to allow for less extensive surgery, but also as a scientific tool, with the use of biomarkers to predict outcomes in adjuvant trials and for the individual patient. This review details the current and most relevant evidence about NET for breast cancer as well as the future directions of this field.
Keywords: breast neoplasm; drug therapy; tamoxifen; aromatase inhibitors